2019
DOI: 10.1016/j.clinthera.2019.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Characteristics, and Patient Burden of Severe Asthma Determined by Using a Japan Health Care Claims Database

Abstract: Background: Recently, several new biological drugs targeting severe asthma are on the market, and various studies on severe asthma have been reported worldwide. However, in Japan, the data are still limited regarding epidemiology and burden of disease on severe asthma. This study determined the prevalence, characteristics, and burden of disease of patients with severe asthma.Methods: : This retrospective study (HO-16-16484) used a nationwide health care claims database. Severity of asthma was defined according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…In this study that included 7,654 newly diagnosed asthma patients, the prevalence of severe asthma was stable during a 1-year follow-up period. Our result of a frequency of 2.7% of patients having severe asthma at 1 year is similar to that of 2.4% reported in a retrospective study performed in Japan that used a nationwide health care claims database [14], but somewhat lower than the commonly reported prevalence of 5-10% [15,16]. In a prior cross-sectional study in China [10], the investigators used different criteria for determining asthma severity that what was used in our study [17].…”
Section: Discussionsupporting
confidence: 85%
“…In this study that included 7,654 newly diagnosed asthma patients, the prevalence of severe asthma was stable during a 1-year follow-up period. Our result of a frequency of 2.7% of patients having severe asthma at 1 year is similar to that of 2.4% reported in a retrospective study performed in Japan that used a nationwide health care claims database [14], but somewhat lower than the commonly reported prevalence of 5-10% [15,16]. In a prior cross-sectional study in China [10], the investigators used different criteria for determining asthma severity that what was used in our study [17].…”
Section: Discussionsupporting
confidence: 85%
“…Severe asthma is estimated to affect 5-10% of the global asthma population and 8-11% of people with asthma in Japan [4,5]. A recent retrospective database study found an association between severe asthma and a significant disease burden in Japanese workers and their family members aged 15-65 years [6]. This study also suggests that Japanese patients with severe asthma are generally older than those with mild or moderate asthma.…”
Section: Introductionmentioning
confidence: 68%
“…The authors, using almost the same definitions as for the present study for asthma and severe asthma, determined that the prevalence of severe asthma was 2.4% among asthma patients. In that study, Meanwhile, the MDV database contains only records from hospitals; therefore, the outpatient visit assessment population of the present study may have included more severe cases than asthma patients in general and resulted in higher prevalence of severe asthma than those for the JMDC database study [6] across all comparable age categories. This study also assessed the burden of outpatient visits for severe asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations